2011
DOI: 10.4103/1119-3077.91765
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomal stricture of the ureter-diagnostic dilemma

Abstract: Chronic schistosomiasis of the urinary tract can present with symptoms unrelated to the disease. A 33-year-old man from Edo State Nigeria presented with recurrent left flank pain. Laboratory investigations did not reveal any cause. Radiological investigation revealed a stricture of the left ureter and hydronephrosis of the left kidney. Management included surgical excision and antischistosomiasis chemotherapy. Histopathological examination of specimen of the ureter obtained after surgical exploration revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…To avoid missing of eggs, the patient was asked to give urine sample between 10:00 am and 2:00 pm when there is a possibility of maximum egg load [6] and each time the urine sample was centrifuged [3,6] but that did not help. Oranusi CK et al observed that in chronic stages excretion of eggs is invariably absent and J Microbiol Infect Dis www.jmidonline.org Vol 9, No 2, June 2019 investigations like bladder biopsy and serology may be more specific [11]. In our case serology was not available and bladder biopsy was not repeated.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…To avoid missing of eggs, the patient was asked to give urine sample between 10:00 am and 2:00 pm when there is a possibility of maximum egg load [6] and each time the urine sample was centrifuged [3,6] but that did not help. Oranusi CK et al observed that in chronic stages excretion of eggs is invariably absent and J Microbiol Infect Dis www.jmidonline.org Vol 9, No 2, June 2019 investigations like bladder biopsy and serology may be more specific [11]. In our case serology was not available and bladder biopsy was not repeated.…”
Section: Discussionmentioning
confidence: 66%
“…In our case also, the pale-yellow color of urine indicated a less severe infection and thus a low egg count. Rare cases of Schistosoma involving unusual sites without suggestive symptoms and absence of eggs in urine and stool have been reported in literature though histopathology of the affected organ in these cases showed presence of eggs [4,[9][10][11]. Studies have shown the percentage of asymptomatic Schistosoma infection to be between 25 and 90 % [13].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] The commonest presenting symptom was recurrent flank pain about 61.9% and this finding is in agreement with studies in Jos (Nigeria) Egypt and Germany. [ 1 6 11 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although rarely encountered, infectious pathologies, iatrogenic causes, ureteral stones, and their subsequent treatment via ureteroscopy and ureteral access sheaths are blamed for ureteral injury and subsequent ureteral strictures. [8][9][10][11][12][13][14] In this Fig. 1.…”
Section: Discussionmentioning
confidence: 99%